THE TEACHING OF LISTENING THROUGH ENGLISH PODCAST AT PRE-INTERMEDIATE PROGRAM OF SEVENTEEN ENGLISH LEARNING - Mujahidin, Mujahidin; Muchyidin, M. Syaichul; Entusiastik, Entusiastik (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
Listening skill has been neglected even if being the most necessary ability in daily communication. It has an important role to improve the students’ language. As learners of English Courses, they need facilities to support their learning process. The podcast is one of the primary facilities by which students are able to develop their scientific and general knowledge. The research intended to describe the preparation, implementation, evaluation, and students’ perceptions of teaching listening through English podcast at the pre-intermediate program of Seventeen English Learning. the research used a qualitative design. The samples are nine students at the pre-intermediate program of Seventeen English Learning. Meanwhile, the instruments used to collect data are an observation checklist, interview guide, and documentation. The collected data are in the form of observation, interview, and documentation. Thus, they are analyzed by using data reduction, data display, and drawing conclusions and verification. The findings showed that the teacher did some preparation before doing the teaching, The teacher also did the learning procedures of teaching listening through the podcast, The teacher as well did evaluation of teaching listening through podcasts started from the beginning, during, and at the end of the learning process. The students’ perceptions after being taught the listening through podcast were positive and it’s able to encourage their speaking, pronunciation, and understanding the speakers’ speech.